ANALYSIS OF LAND COVER (LULC) DYNAMICS OF A SPECIFIC AREA BASED ON GIS AND REMOTE SENSING TECHNOLOGIES - Ahmadjonov Ilknur; Tobirov Odiljon (TADQIQOTLAR, 2025)
Abstract: The assessment of territorial potential based on natural and geographical factors plays a crucial role in sustainable regional planning and resource management. This article explores methodological approaches for evaluating the spatial characteristics of a selected region using Geographic Information Systems (GIS) and related geospatial technologies. The study integrates natural indicators such as relief, climate, land cover, hydrology, and landscape diversity to analyze their spatial distribution and functional significance. GIS-based spatial analysis, thematic mapping, and multi-criteria evaluation methods are applied to identify areas with high potential and development constraints. The results demonstrate that geospatial technologies provide an effective framework for synthesizing heterogeneous environmental data and supporting evidence-based territorial planning. The findings contribute to improving regional assessment methodologies and offer practical insights for sustainable land use planning, environmental management, and sectoral development strategies.